2022
DOI: 10.1017/jfm.2022.330
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution direct simulation of deep water breaking waves: transition to turbulence, bubbles and droplets production

Abstract: We present high-resolution three-dimensional (3-D) direct numerical simulations of breaking waves solving for the two-phase Navier–Stokes equations. We investigate the role of the Reynolds number (Re, wave inertia relative to viscous effects) and Bond number (Bo, wave scale over the capillary length) on the energy, bubble and droplet statistics of strong plunging breakers. We explore the asymptotic regimes at high Re and Bo, and compare with laboratory breaking waves. Energetically, the breaking wave transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 104 publications
(447 reference statements)
17
81
0
Order By: Relevance
“…where Q is the volume of air injected to the breaking cascade per volume of water per second, and can be evaluated from the breaker geometry and energetics [21,22]. The prefactor for the sub-Hinze distribution can then be evaluated using the continuity of N at d h , and…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…where Q is the volume of air injected to the breaking cascade per volume of water per second, and can be evaluated from the breaker geometry and energetics [21,22]. The prefactor for the sub-Hinze distribution can then be evaluated using the continuity of N at d h , and…”
Section: Discussionmentioning
confidence: 99%
“…We now aim to verify that an initial large separation of scales, namely for which d 0 /d h 1, indeed leads to a universal N (d ) ∝ d −3/2 in the sub-Hinze-scale regime. We will analyze laboratory and numerical data of bubble size distribution under breaking waves from previous work [18,22]. On top of this, we compare the results to a more idealized configuration consisting of a single large bubble injected in a turbulent flow, both numerically [39] and experimentally.…”
Section: Experimental Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Giorgio, Pirozzoli & Iafrati (2022) corroborated the findings that the dissipated energy fraction does not depend much on the Reynolds number or dimensionality. Mostert, Popinet & Deike (2022) observed that the Reynolds number does not affect the shape of the bubble size distribution after Re reaches a threshold, as the mean turbulent dissipation rate is not sensitive to Re. The ventilated cavity flows discussed in the present study and the wave breaking flows are both air-water turbulent mixed flow systems.…”
Section: Assessment Of Low-reynolds-number Dns For Insights Into Vent...mentioning
confidence: 95%